Grounding line variability and subglacial lake drainage on Pine Island Glacier, Antarctica - Ian Joughin; David E. Shean; Ben E. Smith; P. Dutrieux (Geophysical Research Letters)
Abstract We produced a 6 year time series of differential tidal displacement for Pine Island Ice Shelf, Antarctica, using speckle‐tracking methods applied to fine‐resolution TerraSAR‐X data. These results reveal that the main grounding line has maintained a relatively steady position over the last 6 years, following the speedup that terminated in ~2009. In the middle of the shelf, there are grounded spots that migrate downstream over the 6 year record. Examination of high‐resolution digital elevation models reveals that these grounded spots form where deep keels (thickness anomalies) advect over an approximately flow‐parallel bathymetric high, maintaining intermittent contact with the bed. These data sets also reveal several subsidence and uplift events associated with subglacial lake drainages in the fast‐flowing region above the grounding line. Although these drainages approximately double the rate of subglacial water flow over periods of a few weeks, they have no discernible effect on horizontal flow speed.